Simulacije - sodobna metoda učenja in poučevanja v zdravstveni negi in babištvu - Karnjuš, Igor (Obzornik zdravstvene nege, 2012)
Introduction: Training of healthcare professionals through simulations is in full swing worldwide, as well in Slovenia. The growing demand for high qualityeducation, the increasing number of students and the ever rising demands for patient safety lead to the application of simulations into the nursing and midwifery study programs. The bases for a qualitative implementation of simulation are: an appropriate simulator, a simulation basedlearning environment comparable to the clinical environment, and highly qualified teaching staff. The aim of this article is to present simulation as learning and teaching method in nursing and midwifery, as well as to encouragethe professional public to reflect on the active implementation of simulation in the health care education process. Methods: Literature review was conducted to survey research done in the field of simulation as teaching and learning method in nursing and midwifery, published between 2000 and 2011.The ScienceDirect, ProQuest, Sage, Medline, CINAHL and COBIB.SI databaseswere the resources consulted. Discussion and conclusions: Although simulation cannot fully compensate for training in a clinical setting, it provides and enhances new educational opportunities in nursing and midwifery and may contribute to a higher level of professional competence and skills of nurses and midwives.
Keywords: babištvo; education; izobraževanje; midwifery; nursing; simulacije; simulation; zdravstvena nega